Changes in working memory induced by lipopolysaccharide administration in mice are associated with metabotropic glutamate receptors 5 and contrast with changes induced by cyclooxygenase-2: Involvement of postsynaptic density protein 95 and down syndrome cell adhesion molecule - Stachowicz, Katarzyna; Pańczyszyn-Trzewik, Patrycja; Sowa-Kućma, Magdalena; Misztak, Paulina (Neuropeptides (Edinburgh), 2023)
The strength and quality of the signal propagated by the glutamate synapse (Glu) depend, among other things, on the structure of the postsynaptic part and the quality of adhesion between the interacting components of the synapse. Postsynaptic density protein 95 (PSD95), mammalian target of rapamycin (mTOR), and Down syndrome cell adhesion molecule (DSCAM) are components of the proper functioning of an excitatory synapse. PSD95 is a member of the membrane-associated guanylate kinases protein family, mainly located at the postsynaptic density of the excitatory synapse. PSD95, via direct interaction, regulates the clustering and functionality of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) and N-methyl-D-aspartic acid (NMDA) receptors at a synapse. Here, the effects of treatment with an antagonist of mGluR5 (MTEP) and NS398 (cyclooxygenase-2, COX-2 inhibitor) on PSD95, mTOR, and DSCAM in the hippocampus (HC) of C57B1/6 J mice using Western blots in the context of learning were examined. Moreover, the sensitivity of selected proteins to lipopolysaccharide (LPS) was monitored. MTEP injected for seven days induced upregulation of PSD95 in HC of mice. The observed effect was regulated by a COX-2 inhibitor and concurrently by LPS. Accompanying alterations in DSCAM protein were found, suggesting changes in adhesion strength after modulation of glutamatergic (Glu) synapse via tested compounds.